Penyuluhan Pengendalian Stok Produk dalam Memenuhi Jumlah Permintaan Bakso di UD Hani Jatirejo - Zenita Afifah Fitriyani; Mokhamad Ridha; Fajar Budiyanto; Ulfa Rahmawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Meatballs are one of the popular processed meat products, easy to find, and liked by the public. Meatballs can also be stored for a long time, so business actors do not need to worry about the quality of the meatballs being damaged, so the production and operational processes need to be carried out properly. The high demand for meatball orders occurs on certain days, the stock of meatballs tends to be less than satisfactory. The purpose of this community service is to provide an understanding to UD. Hani Jatirejo so that they can control product stock, so that consumer demand for products can be met. The methods used in this training are the Preparation Stage, the Implementation Stage, and the Evaluation Stage. The results of this service are the implementation of visits and observations on the operation and production of meatball making, as well as the provision of product stock control counseling in meeting the number of customer requests UD. Hani Jatirejo.